The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1987
DOI: 10.1590/s0074-02761987000800064
|View full text |Cite
|
Sign up to set email alerts
|

Specific treatment of advanced Schistosomiasis liver disease in man: favourable results

Abstract: One hundred eighty-four patients with hepatosplenic schistosomiasis mansoni from the northeast of Brazil were studied. All were treated with a single dose of Oxamniquine or Praziquantel, and were observed over 6 to 12 months. Special attention was given to the evolution of severe hepatopathy. Favourable results were obtained, particularly with the compensated hepatosplenic form. Hepatic function showed great improvement. Hepatomegaly and splenomegaly were significantly reduced in size, to a greater or lesser e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Many studies have been conducted in an attempt to evaluate the aspects of immunity that might be impaired, but the mechanisms are not perfectly understood yet 10,11,15,21,22,28,29,34,36,50,54,55,59,60 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted in an attempt to evaluate the aspects of immunity that might be impaired, but the mechanisms are not perfectly understood yet 10,11,15,21,22,28,29,34,36,50,54,55,59,60 .…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the putative effect of ASC on the control of inflammation and induction of tissue regeneration, we designed our study linking the known anti-parasite effect of PZQ with the ASC properties to determine whether combined PZQ and ASC therapy would induce a faster recovery than the treatment with PZQ alone. The modulation of granulomas and tissue repair in some S. mansoni infected individuals [62] can take a long time when PZQ is used as the only therapy [19,63]. Therefore, the possible effect of ASC on controlling inflammation and reducing liver fibrosis could be an important adjunct treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low cost, safety and high efficacy, PZQ has been used as the gold-standard treatment against schistosomiasis, and its mass administration has become the mainstay of national control programs [18]. Currently, there is no specific treatment to control the granulomatous reaction and hepatosplenic clinical form of the disease, which might continue for several months after successful treatment with PZQ [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that specifi c treatment for S. mansoni can contribute to decreasing infection levels and improving clinical conditions such as hepatosplenomegaly and PPF [15][16][17] . As a result, the regression of PPF may prevent the emergence of portal hypertension, highlighting the importance of PPF diagnosis by obtaining accurate methods for monitoring this disease 18 .…”
Section: Discussionmentioning
confidence: 99%